Agricultural to urban water transfers in Colorado: an assessment of the issues and options - Rice, Teresa A., author; MacDonnell, Lawrence J., author; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 1993)
With constrains on the additional development of water supplies and in the face of growing urban demands for water cites have increasingly been turning to the water transfer process as a means of expanding their supplies. Urban encroachment onto formerly irrigated croplands long has caused the use of irrigation water to change to urban use. To make the transfers economically warranted the size of the transfers tends to be large. This transfer of large quantities of water from often rural areas with little alternative economic opportunity is prompting many western states to revisit their water transfer laws. This report examines approaches taken in the western states to both better facilitate the water transfer process and better address so-called third party effects. The report focuses initially on water transfer law and procedure in Colorado and notes that Colorado emphasizes a single kind of transaction--one in which there is a permanent purchase of a water right and a consequent total cessation of the associated activity. The report then provides a detailed evaluation of a variety of approaches used in other western states involving (1) conditioning water transfers, (2) requiring reduced water use, (3) providing incentives to conserve, and (4) facilitating short-term transfers. Finally recommendations are made for changes in Colorado law and procedure providing incentives to save water, establishing water banks, and addressing third party effects.
December 1993.
This publication is a product of the Natural Resources Law Center, a research and public education center at the University of Colorado School of Law.
Keywords: Water transfer -- Law and legislation -- Colorado; Water transfer -- Law and legislation -- West (U.S.); Water resources development -- Government policy -- Colorado; Municipal water supply -- Colorado; Water use -- Colorado